ANALYSIS OF EXISTING BIOREACTORS WITH IMMOBILIZED MICROORGANISMS: Array - Mel’nick, V.; Rhuzinska, L.; Vorobiova, O. (Municipal economy of cities (Technical science), 2019)
This review article describes the current state of the industry of immobilized cells and the development of bioreactors with immobilized cells and carrier materials for immobilization. On the basis of literature analysis, a classification of constructions of bioreactors with immobilized cells is proposed, depending on the location of cellular aggregates: suspended particles, fixed particles and moving surfaces used with immobilized cells. The modern development of biotechnological production requires new approaches to the implementation of biosynthesis processes. The performance of bioreactors in the production of various target products depends on the efficiency of the use of biological agents, which depends on the process conditions. One of the ways to improve the performance of fermentation is cell immobilization, which provides the possibility of continuous processing, cell stability, reducing the cost of recovery, recycling and further processing. Immobilization of cells protects them from landslide efforts that may occur during the operation of the bioreactor. At the same time, the industrial use of immobilized cells is still limited and their further application requires a detailed analysis of the specific features of the designs of bioreactors with immobilized cells and carrier materials for immobilization. At present, there is a large variety of immobilization methods, but they can be conventionally divided into chemical, physical and mechanical. The most widespread mechanical method was the inclusion of cells in the composition of gels, membranes and fibers. Consequently, for the wider introduction of methods and equipment using immobilized cells in biotechnological and pharmaceutical industries, further research is required on how to immobilize cells on a variety of carriers.